Spent Bleaching Earth Recovery of Used Motor-Oil Refinery - Sabour, Mohammad Reza; Shahi, Mahsa (Salehan Institute of Higher Education, 2018)
Bleaching earth refers to natural or activated clay which has the capacity to adsorb colored materials and other impurities during oil purification processes. This research utilized the spent bleaching earth (SBE) in used motor oil purification process via thermal remediation (650 ËC) and acid washing methods (1 M HCl). Then, the activated spent bleaching earth (ASBE) was characterized. The results obtained from the BET analysis show the specific surface area and pore volume of the ASBE, activated virgin bleaching earth (AVBE) and virgin bleaching earth (VBE). These parameters are 100.38 m2g-1 and 0.23 cm3g-1 for the activated spent bleaching earth, 100.82 m2g-1 and 0.22 cm3g-1 for the activated virgin bleaching earth and 83.34 m2g-1 and 0.19 cm3g-1 for the virgin bleaching earth. The BJH analysis indicates that SBE activation increases mesopores in ASBE. In addition, results obtained from the XRD and FTIR tests illustrate that activation of SBE does not affect the physical and chemical properties of montmorillonite clay. Furthermore, SEM observations indicate surface morphology improvement in ASBE. Hence, activation of earth enhances its adsorption efficiency in comparison with virgin bleaching earth.